Caracterização do óxido formado na superfície da junta M5TM/Zircaloy- 4 soldada por resistência e pressão após testes de corrosão em autoclave a 360°C - Soares, Alexandre Roberto (Universidade Federal de São Carlos, 2024)
The nuclear fuel cycle involves uranium mining and chemistry, fuel manufacturing, fuel element operation in reactors, and post-irradiation treatment. The casing tubes are produced with zirconium alloys, as they have a low neutron capture cross-section. Welding processes in nuclear applications are electron beam, laser, resistance, projection and spot welding. The welds undergo destructive and non-destructive tests to characterize the joint, tube bursting tests, metallography, and corrosion. The present work sought to characterize the oxide layer formed on the surface of a joint composed of zirconium M5TM and Zircaloy-4 alloys welded by the Resistance Pressure Welding (RPW) process. Autoclave corrosion tests were carried out to simulate operational conditions, identifying specific oxidation/corrosion mechanisms after analysis. The results obtained show that during the corrosion process, both the surface of the plug and the tube oxidize, forming an oxide layer composed predominantly of the m-ZrO2 phase, adhering and continuing on the surface of both materials. Furthermore, small Zr(Fe,Cr)2 precipitates present in the buffer microstructure oxidize, remaining on the surface of the oxide layer. For the welded bead, the rapid growth of the oxide leads to the formation of a continuous nodule of white oxide, which presents a high fraction of the t-ZrO2 phase. The growth of this white oxide nodule is accompanied by the penetration of the oxide into the bead reinforcement at the plug/weld bead interface region. As the corrosion process progresses, complete oxidation of the Zr(Fe,Cr)2 precipitates occurs, leading to the formation of voluminous oxide nodules composed of a mixture of phases: t-ZrO2, m-ZrO2, Cr2O3 and Fe2O3. Although the oxides observed were obtained under more severe conditions than usual, they proved to be safe in terms of depth and thickness, not drastically affecting the weld bead region even after five corrosion cycles.
Characterization of the oxide formed on the surface of the M5TM/Zircaloy-4 joint welded by resistance and pressure after corrosion tests in an autoclave at 360°C
Keywords: Corrosão em autoclave; Ligas de zircônio; Processos de soldagem resistance pressure welding (RPW); Óxido branco; Corrosion in autoclave; Zirconium alloys; Resistance pressure welding (RPW) process; White oxide; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; ENGENHARIAS::ENGENHARIA NUCLEAR::COMBUSTIVEL NUCLEAR